Atrial fibrillation: villain or bystander in vascular brain injury. (6th December 2020) - Freedman, Ben; Kamel, Hooman; Van Gelder, Isabelle C; Schnabel, Renate B
Abstract: Atrial fibrillation (AF) and stroke are inextricably connected, with classical Virchow pathophysiology explaining thromboembolism through blood stasis in the fibrillating left atrium. This conceptualization has been reinforced by the remarkable efficacy of oral anticoagulant (OAC) for stroke prevention in AF. A number of observations showing that the presence of AF is neither necessary nor sufficient for stroke, cast doubt on the causal role of AF as a villain in vascular brain injury (VBI). The requirement for additional risk factors before AF increases stroke risk; temporal disconnect of AF from a stroke in patients with no AF for months before stroke during continuous ECG monitoring but manifesting AF only after stroke; and increasing recognition of the role of atrial cardiomyopathy and atrial substrate in AF-related stroke, and also stroke without AF, have led to rethinking the pathogenetic model of cardioembolic stroke. This is quite separate from recognition that in AF, shared cardiovascular risk factors can lead both to non-embolic stroke, or emboli from the aorta and carotid arteries. Meanwhile, VBI is now expanded to include dementia and cognitive decline: research is required to see if reduced by OAC. A changed conceptual model with less focus on the arrhythmia, and more on atrial substrate/cardiomyopathy causing VBI both in the presence or absence of AF, is required to allow us to better prevent AF-related VBI. It could direct focus towards prevention of the atrial cardiomyopathy though much work is required to better define this entity before the balance between AF as villain or bystander can be determined.